Policies to Decarbonize Industry While Addressing Competitiveness and Carbon Leakage - Ian Parry; Simon Black; Danielle Minnett; Karlygash Zhunussova (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
This paper discusses the attributes and design of alternative mitigation instruments for the industrial sector, their competitiveness and emissions leakage impacts, and supplementary measures to address these effects. A quantitative analysis indicates, for selective countries, production cost increases under a 50 per tonne unilateral CO2 price in 2030 are 4-8 percent for steel, 20-30 percent for chemicals, and 30-35 percent for cement with leakage rates of 20-50 percent across these industries. Competitiveness and leakage impacts are however much smaller under pricing with border adjustments, other mitigation instruments like feebates and performance standards, or internationally coordinated pricing.
Keywords: Q31; Q35; Q48; H23; 330; climate mitigation; carbon pricing; competitiveness; emission leakage; border carbon adjustment; feebates